Cytoprotective and Antioxidant Effects of Steen Solution on Human Lung Spheroids and Human Endothelial Cells. Issue 7 (26th April 2017) - Pagano, F.; Nocella, C.; Sciarretta, S.; Fianchini, L.; Siciliano, C.; Mangino, G.; Ibrahim, M.; De Falco, E.; Carnevale, R.; Chimenti, I.; Frati, G.
Abstract : Respiratory diseases represent a major healthcare burden worldwide. Lung transplantation (LTx) is the "gold standard" for end‐stage patients, strongly limited by shortage of available/suitable donor lungs. Normothermic ex vivo lung perfusion (EVLP) has significantly increased the number of lungs suitable for transplantation. Steen solution is used for EVLP, but the mechanisms involved in its beneficial properties remain to be clarified. We investigated the effects of Steen solution in an in vitro protocol of cold starvation and normothermic recovery on human lung spheroids, named pneumospheres (PSs), containing epithelial/basal cells, and on endothelial human umbilical vein endothelial cells (HUVEC). Steen solution significantly preserved the viability of PSs, reduced reactive oxygen species (ROS) release by PSs and HUVECs, decreased NADPH‐oxidase (NOX) activity in PSs, and reduced inflammatory cytokines expression levels in HUVECs. Steen solution was able to specifically reduce NADPH oxidase 2 (NOX2) isoform activation, particularly in PSs, as detected by soluble‐NOX2 peptide and p47‐phosphorylation. Interestingly, a specific NOX2 inhibitor could partly mimic the pro‐survival effect of Steen on PSs. We provide the first evidence that Steen solution can preserve lung epithelial/progenitor cells viability partially through NOX2 downregulation, and exert antioxidant effects on parenchymal cells, with consequent ROS reduction. These results suggest that NOX2 inhibition might be an additional strategy to reduce cellular damage during LTx procedures. Abstract : In this study, the Steen solution, used for ex vivo lung perfusion protocols, exerts cytoprotective and antioxidant effects on human lung epithelial cells and human endothelial cells.